Synthesis and Antimicrobial Activity of New N-Methyl- N-(2-pyridyl) Aromatic and Heteroaromatic Hydrazones - ABU-EL-HALAWA, RAJAB; AL-NURI, MOHAMED; MAHMOUD, FOUAD (Asian Journal of Chemistry, 2010)
Aromatic and heteroaromatic N-methyl-N-(2-pyridyl)-hydrazones 3a-f were synthesized and characterized by elemental analyses and spectral data. 1H, 13C NMR and mass spectra supported the formation of the E-isomer. N-Methyl-N-(2-pyridyl)hydrazone carboxaldehydes can be readily characterized by mass spectrometry. The new hydrazones 3a-h have been screened for antimicrobial activity.